2008
DOI: 10.1016/j.bbmt.2008.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Mobilization with Cyclophosphamide Overcomes the Suppressive Effect of Lenalidomide Therapy on Stem Cell Collection in Multiple Myeloma

Abstract: A total of 28 treatment-naïve patients with stage II or III multiple myeloma (MM) were treated with the combination of clarithromycin, lenalidomide, and dexamethasone (BiRD). Stem cells were collected following granulocyte- colony stimulating factor (G-CSF) or cyclophosphamide (Cy) plus G-CSF mobilization at maximum response. Sufficient stem cells for 2 autologous stem cell transplants were collected from all patients mobilized with Cy plus G-CSF, versus 33% mobilized with G-CSF alone (P<.0001). The duration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
84
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 18 publications
2
84
0
7
Order By: Relevance
“…Overall, the patients were characterized by features that are known to affect standard stem cell mobilization negatively, including advanced age, a diagnosis of NHL, previous radiotherapy, extensive treatment with chemotherapy, treatment with lenalidomide or purine analogues, previous autoSCT, or failure of at least one previous attempt at mobilization [7][8][9][10][11][12][13][14][15]. We observed that, despite these unfavorable characteristics, mobilization with plerixafor and G-CSF enabled the required number of stem cells to be collected in 67.5% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the patients were characterized by features that are known to affect standard stem cell mobilization negatively, including advanced age, a diagnosis of NHL, previous radiotherapy, extensive treatment with chemotherapy, treatment with lenalidomide or purine analogues, previous autoSCT, or failure of at least one previous attempt at mobilization [7][8][9][10][11][12][13][14][15]. We observed that, despite these unfavorable characteristics, mobilization with plerixafor and G-CSF enabled the required number of stem cells to be collected in 67.5% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, the data reveal that mobilization with CY and filgrastim results in an increased number of CD34 þ cells collected and reduced rate of mobilization failure when compared with mobilization with filgrastim alone. 12,13 Additionally, it has been demonstrated that the majority of lenalidomide-treated MM patients who fail filgrastim mobilization will yield an adequate number of CD34 þ cells when subjected to CY plus filgrastim mobilization. 11 Therefore, the upfront use of CY and filgrastim mobilization can partially overcome the detrimental effect of lenalidomide even though it is associated with substantial morbidity and still carries a failure rate of approximately 10%.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] The use of the IMID lenalidomide in the induction regimen was early identified as a risk factor for poor AHSC mobilization. [7][8][9][10] This negative effect, noticed particularly with growth factor mobilization, is at least partially overcome with the use of chemotherapy mobilization, [11][12][13] although this strategy carries higher cost and toxicity. [14][15][16][17] The CXCR4-SDF1-binding inhibitor plerixafor dramatically enhances filgrastim-based CD34 þ mobilization in patients with MM, 18 but is expensive, limiting its use in all patients undergoing mobilization.…”
Section: Introductionmentioning
confidence: 99%
“…12 LEN is not toxic to HPCs, and CY is able to overcome mobilization failures after LEN treatment. 13 Silvennoinen et al 1 report here the results of a prospective, randomized study comparing low-dose CY 2 g/m 2 +G-CSF (arm A) with G-CSF alone (arm B), after a short course LEN-based induction in 80 MM patients. The primary endpoint was the proportion of patients achieving a yield of more than 3 × 10 6 /kg CD34+ cells with less than three aphereses.…”
mentioning
confidence: 99%